Sexual assault interventions may be doing more harm than good with high-risk males. (July 2018) - Malamuth, Neil M.; Huppin, Mark; Linz, Daniel
Abstract: Based on legal requirements and other considerations, there have been many well-meaning interventions intended to reduce sexual assault on university campuses throughout the US. There is no legal requirement, however, to evaluate the effectiveness of these programs, and few evaluations have been conducted. Those that have suggest that at best only a small number of these interventions have been effective and those involve bystander interventions. More importantly, there has been very little research examining the effects of such interventions on men at high risk for sexual aggression, who presumably are a key target of such interventions. Research on similar campaigns in other domains should have alerted investigators to the possibility of boomerang reactance effects wherein interventions can actually have the opposite of the intended effects for high-risk college males. The few studies that directly have examined this possibility indeed are supportive of the substantial likelihood of such negative effects. Commonly used interventions may fail with high-risk men because they are likely to generate "hostility reactance" — one of the key causes of both sexual violence itself and the unintended adverse effects of the interventions. We address the question of why universities have failed to address this possible effect of interventions and why previous reviews have not highlighted this possible danger. Highlights: With high-risk men, currently used sexual assault interventions are problematic. These interventions appear to be having opposite than intended effects. Such boomerang effects are likely due to these men's hostile reactance. Reactance may underlie both their sexual violence and responses to interventions. Failure to acknowledge this danger may be due to a lack of suitable strategy.